Estuarine Floc Mass Distributions from Aggregation/Disaggregation and Bed Sediment Exchange - William H. McAnally; Ashish J. Mehta; Andrew J. Manning; Carola Forlini (Journal of Marine Science and Engineering)
Estuarine benthos, among other lifeforms of interest to water quality, can be sensitive to size-distributed suspended cohesive flocs. In such a context, tide-dependent floc mass distributions in the Tamar Estuary in the UK are revisited. At the field site close to maximum turbidity, time-series of the water level, current velocity, salinity, and suspended sediment concentration (SSC) were recorded in 1998 over several tidal cycles. Concurrently, at selected times and elevation, floc mass distributions were derived from in situ observations of the SSC, floc diameters, and settling velocities. A previously developed time-dependent model, revised to account for both multiclass floc aggregation/disaggregation and bed sediment exchange by erosion and deposition, is applied to simulate mass distributions during ebb/flood cycles on 24 June and 5 August. Although the model does not account for the density effects of salinity or sediment advection, limited comparisons between simulated and observed mass distributions indicate generally good agreement in median diameter prediction on both days. This concurrence is due to the primary role of suspended floc dynamics and only a secondary contribution from bed sediment exchange in governing floc properties. For a better prediction of the SSC variation with the tide, the effects of salinity and advection can be incorporated by coupling the modeled floc dynamics with a suitable multi-dimensional hydrodynamic code.